2018
DOI: 10.1016/j.bjm.2017.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of root-knot nematode disease control and plant growth promotion potential of biofertilizer Ning shield on Trichosanthes kirilowii in the field

Abstract: Biofertilizer Ning shield was composed of different strains of plant growth promotion bacteria. In this study, the plant growth promotion and root-knot nematode disease control potential on Trichosanthes kirilowii in the field were evaluated. The application of Ning shield significantly reduced the diseases severity caused by Meloidogyne incognita, the biocontrol efficacy could reached up to 51.08%. Ning shield could also promote the growth of T. kirilowii in the field by increasing seedling emergence, height … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…They observed that plants treated with S. antibioticus strain M7 showed an enhancement in the levels of pigments due to triggered photosynthetic activities of plants. Moreover, a study reported by Jiang, et al [ 61 ], also revealed that Trichosanthes kirilowii plants infested with nematodes showed an increase in pigment levels upon microbial inoculations. Another study reported by Khanna, et al [ 57 ] suggested that stimulatory effects in their photosynthetic apparatus are due to microbe mediated upregulation in the enzymes responsible for pigment synthesis.…”
Section: Discussionmentioning
confidence: 90%
“…They observed that plants treated with S. antibioticus strain M7 showed an enhancement in the levels of pigments due to triggered photosynthetic activities of plants. Moreover, a study reported by Jiang, et al [ 61 ], also revealed that Trichosanthes kirilowii plants infested with nematodes showed an increase in pigment levels upon microbial inoculations. Another study reported by Khanna, et al [ 57 ] suggested that stimulatory effects in their photosynthetic apparatus are due to microbe mediated upregulation in the enzymes responsible for pigment synthesis.…”
Section: Discussionmentioning
confidence: 90%
“…B. subtilis SM21 is able to colonize and form a biofilm on tomato root surface and control plant disease ( Chen et al., ; Wang et al., ). XY21 was selected for controlling tomato bacterial wilt caused by Ralstonia solanacearum ( Xue et al., ) The consortium generates synergistic activity in controlling different plant diseases such as cotton Verticillium wilt and root‐knot nematode disease ( Yang et al., 2014; Jiang et al., ), and promotes plant resistance to chilling stress ( Wang et al., ). The control efficiency of both pre‐ and post‐harvest disease and the growth promotion, influence on pepper fruit yield and quality, as well as on soil fertility were determined in the present study.…”
Section: Introductionmentioning
confidence: 99%
“…They are by far the most formidable, polyphagous that attack the majority of crops resulting in a significant decline in yield. This crop loss has been estimated globally at 14% per year (Groover and Lawrance, 2018), 15-25% or even 75% in some cases according to Jiang et al (2018) great power of multiplication allowing them to quickly invade the roots of the plants on which they cause galls. In terms of money, Phani et al (2017) have estimated the damage caused by these nematodes globally to 173 million Dollars by year.…”
Section: Introductionmentioning
confidence: 99%